2021
DOI: 10.1101/2021.05.24.445335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein unlikely to bind to integrins via the Arg-Gly-Asp (RGD) motif of the Receptor Binding Domain: evidence from structural analysis and microscale accelerated molecular dynamics

Abstract: The Receptor Binding Domain (RBD) of SARS-CoV-2 virus harbors a sequence of Arg-Gly-Asp tripeptide named RGD motif, which has also been identified in extracellular matrix proteins that bind integrins as well as other disintegrins and viruses. Accordingly, integrins have been proposed as host receptors for SARS-CoV-2. The hypothesis was supported by sequence and structural analysis. However, given that the microenvironment of the RGD motif imposes structural hindrance to the protein-protein association, the va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…SARS-CoV-2 contains an ‘RGD’ amino acid motif in the spike receptor binding domain (RBD) ( Supplementary Fig. S14A ), and this motif commonly binds cell surface integrins ( Makowski, Olson-Sidford, and Weisel 2021 ), although one molecular dynamics microscale simulation study disputes the involvement of the spike RGD in integrin binding ( Othman et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 contains an ‘RGD’ amino acid motif in the spike receptor binding domain (RBD) ( Supplementary Fig. S14A ), and this motif commonly binds cell surface integrins ( Makowski, Olson-Sidford, and Weisel 2021 ), although one molecular dynamics microscale simulation study disputes the involvement of the spike RGD in integrin binding ( Othman et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is growing evidence for interactions based on the spike RGD sequence, the exact binding mechanisms are still unknown ( Robles et al, 2021 ; Simons et al, 2021 )⁠. Additionally, previous preliminary computational studies suggest that the spike RGD motif is not completely accessible for integrin-binding, while there have also been other non-RGD-binding integrins that have been suggested to be potentially involved in SARS-CoV-2 viral entry ( Othman et al, 2021 ; Wang et al, 2021 ). An analysis of putative non-RGD integrin-binding motifs on the SARS-CoV-2 receptor-binding domain identified several viable candidates after sequence alignment and subsequent structural characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the canonical SARS-CoV-2 cell entry receptor, ACE2, has been shown to associate with α 5 β 1 integrins, potentially facilitating virus internalization ( Beddingfield et al, 2021 ; Kliche et al, 2021 )⁠. A structure-based computational study has indicated that the RGD motif accessibility to integrins depends based on its depth within the spike receptor-binding domain ( Othman et al, 2021 ). The study performed protein-protein docking between the spike protein and α 5 β 1 , α IIb β 3 , and α V β 8 integrins and found that the interactions were not favourable, thus suggesting that other motifs on the spike receptor-binding domain may be involved in interactions with integrins.…”
Section: Introductionmentioning
confidence: 99%
“…3 ). R403 generates a potential RGD integrin binding site in the viral Spike protein and it is under debate whether the ability of the SARS-CoV-2 S to use integrins as viral attachment factors may play a role in its high infectiousness 18,19 . The integrin inhibitor ATN-161 had no significant effect on SARS-CoV-2 or T403R RaTG13 S-mediated infection ( Extended Data Fig.…”
mentioning
confidence: 99%